Clinical outcomes of sharp esophageal foreign bodies in elderly patients: a retrospective study from Wuhan, China - Xu, Jiahang; Chen, Baojun; Liu, Yong (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to explore the clinical characteristics, treatment determinants, and outcomes of elderly patients with sharp esophageal foreign bodies (EFBs) in Wuhan, China.MethodWe conducted a retrospective analysis of 58 elderly patients (≥65 years) with sharp EFBs treated at Wuhan Central Hospital from January 2017 to June 2023. Patients were allocated to either an endoscopic (n = 43) or surgical (n = 15) treatment group based on clinical severity. We analyzed demographics, EFB type, injury severity, pre-hospital delay, laboratory findings, length of hospital stay, and functional outcomes using the Barthel Index. Statistical comparisons, including effect sizes and 95% confidence intervals, were performed, and a multivariable logistic regression analysis was conducted to identify independent predictors for surgical intervention.ResultsNo significant differences were observed in baseline demographics (p > 0.05). Fish bones (60.3%) were the most common EFB. Factors significantly associated with requiring surgical treatment included longer pre-hospital delay (median 3.0 vs. 0.5 days, p < 0.001), presence of fever (60.0% vs. 4.7%, p < 0.001), leukocytosis (46.7% vs. 16.3%, p = 0.031), dysphagia (20.0% vs. 2.3%, p = 0.041), and pre-existing esophageal diseases (53.3% vs. 14.0%, p = 0.004). All patients in the surgical group had esophageal perforation or a peri-esophageal abscess, compared to only 25.6% in the endoscopic group (p < 0.001). Multivariable analysis identified pre-hospital delay (OR 2.55, 95% CI [1.29–5.04]) and presence of fever at admission (OR 15.8, 95% CI [3.01–82.9]) as independent predictors for surgery. Endoscopic treatment was associated with a significantly shorter hospital stay (mean 4.3 vs. 13.7 days, p < 0.001) and superior functional recovery at discharge (p = 0.008) and 1 month post-procedure (p < 0.001).ConclusionDelayed medical consultation, severe complications like perforation and abscess, and underlying esophageal comorbidities are key factors necessitating surgical intervention for sharp EFBs in the elderly. Fever at admission and pre-hospital delay are strong independent predictors of the need for surgery. Prompt diagnosis and endoscopic management, when feasible, are associated with shorter hospitalizations and better functional outcomes.